2022
DOI: 10.1186/s12876-022-02576-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of NAFLD and MAFLD diagnostic criteria in contemporary urban healthy adults in China: a cross-sectional study

Abstract: Background A recently proposed diagnostic criteria of metabolic dysfunction-associated fatty liver disease (MAFLD) is more available for various clinical situations than nonalcoholic fatty liver disease (NAFLD), but understanding about differences between NAFLD and MAFLD in clinical practice remains limited in the general adult urban population in China. Methods A total of 795 subjects were recruited from Wu Song Branch of Zhongshan Hospital who pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…7 Recent studies have shown that the criteria for MAFLD are more accurate in identifying patients with high risk of fatty liver disease compared to the NAFLD criteria. [8][9][10] Therefore, the impact of metabolic dysfunction on the natural progression of liver diseases such as chronic viral hepatitis or alcoholic hepatitis is studied using the MAFLD criteria. 4 In the western countries, MAFLD is one of the leading causes of end-stage liver disease, cirrhosis, and hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recent studies have shown that the criteria for MAFLD are more accurate in identifying patients with high risk of fatty liver disease compared to the NAFLD criteria. [8][9][10] Therefore, the impact of metabolic dysfunction on the natural progression of liver diseases such as chronic viral hepatitis or alcoholic hepatitis is studied using the MAFLD criteria. 4 In the western countries, MAFLD is one of the leading causes of end-stage liver disease, cirrhosis, and hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…As NAFLD and MAFLD highly overlap (21), the results of this study may have been similar to those of a previous study on AIH patients with NAFLD. Previous reports have shown that MAFLD is more likely to progress to liver fibrosis than NAFLD is (22)(23)(24). Therefore, further studies are needed to reveal the differences in the impact of NAFLD and MAFLD on AIH.…”
Section: Discussionmentioning
confidence: 96%
“…Due to recent changes in the nomenclature, MASLD covers a broad spectrum of pathological changes in liver parenchyma regarding hepatic steatosis [17,18]. Compared to previous NAFLD or MAFLD nomenclature and the fact that some patients might have average values of liver enzymes as being routinely checked in primary healthcare until ultrasound is used to spot specific parenchymal steatotic changes, the use of MASLD criteria increases the pool of T2DM patients being leaned towards metabolic illness [1,17].…”
Section: Discussionmentioning
confidence: 99%